The outcome of stroke: A six month follow-up study - Ismail, Kameran Hassan (Zanco Journal of Medical Sciences (ZJMS), 2018)
Background and objective: Stroke is an increasing problem in developing countries and is the principal cause of disability and dependency in the western world. This study aimed to find out the one- and six-month case fatality, dependency and recurrence rates of stroke in Erbil teaching hospitals. Methods: This hospital-based prospective study included 293 stroke patients hospitalized in Erbil teaching hospitals from January 1st, 2015 through December 31st, 2015. Stroke was diagnosed by a consultant internist or neurologist and confirmed by brain CT-scan and/or MRI. Patients were followed-up for six months, then one- and six-month outcomes were measured including case-fatality, dependency and recurrences rates. Results: The one and six month case fatality rates were 28.3% and 37.5%, respectively. The rates in females (33.3%, 42.6%, respectively) were higher than that in males (23.7%, 32.9%, respectively), but there was no significant association between case-fatality rate and gender. A total of 74.3% and 45.4% of patients at one- and six-month were functionally dependent. The majority (88.9%) of diabetic patients were functionally dependent. Also, the one and six month recurrence rates of stroke patients were 15.7% and 23.2%, respectively. For both one and six month post stroke more recurrence occurred from ischemic (16.2%, 14.3%, respectively) than from hemorrhagic (24.5%, 19.5%, respectively) strokes, but there was no significant association between the recurrence and stroke subtype (P = 0.691, P = 0.367, respectively). Conclusion: The reported outcomes are relatively comparable to that reported in other developing countries, although it is still more than the rates of developed countries. Outcome measures can help to give information and develop guidelines for clinical practice and research.